Asymmetric Dimethylarginine and Reactive Oxygen Species: Unwelcome Twin Visitors to the Cardiovascular and Kidney Disease Tables - Wilcox, Christopher S. (Hypertension (Dallas, Tex. 1979), 2012)
Plasma levels of asymmetric dimethylarginine or markers of reactive oxygen species are increased in subjects with risk factors for cardiovascular disease or chronic kidney disease. We tested the hypothesis that reactive oxygen species generate cellular asymmetric dimethylarginine that together cause endothelial dysfunction that underlies the risk of subsequent disease. Rat preglomerular vascular smooth muscle cells transfected with p22 had increased NADPH oxidase activity, enhanced activity and expression of protein arginine methyltransferase, and reduced activity and protein expression of dimethylarginine dimethylaminotransferase and of cationic amino acid transferase 1 resulting in increased cellular levels of asymmetric dimethylarginine. Rats infused with angiotensin II had oxidative stress. The endothelial function of their mesenteric arterioles was changed from vasodilatation to vasoconstriction, accompanied by increased vascular asymmetric dimethylarginine. All of these changes were prevented by Tempol. In vivo silencing of dimethylarginine dimethylaminotransferase 1 increased plasma levels of asymmetric dimethylarginine, whereas silencing of dimethylarginine dimethylaminotransferase 2 impaired endothelial function. We suggest that initiation factors, such as angiotensin II, expressed in blood vessels or tissues of subjects with cardiovascular and kidney disease risk factors generate reactive oxygen species from NADPH oxidase that enhances cellular asymmetric dimethylarginine in an amplification loop. This leads to adverse changes in vascular and organ functions, as a consequence of reduced tissue levels of NO and increased reactive oxygen species. Thus, we conclude that reactive oxygen species and asymmetric dimethylarginine form a tightly coupled amplification system that translates cardiovascular/kidney risk into overt disease.